The global groundwater situation: overview of opportunities and challenges - Shah, Tushaar; Molden, David J.; Sakthivadivel, Ramaswamy; Seckler, D. (International Water Management Institute, 2000)
Groundwater offers us few but precious opportunities for alleviating the misery of the poor; but it poses many?and daunting?challenges of preserving the resource itself. A big part of the answer is massive initiatives to augment groundwater recharge in regions suffering depletion; but, in the ultimate analysis, these cannot work without appropriate demand-side interventions. The water vision of a world that future generations will inherit will have to be the one in which groundwater plays its full developmental, productive and environmental role but in a sustainable manner; and the framework of action to realize this vision will mean eschewing the current free-for-all in groundwater appropriation and use, and promoting a more responsible management of this precious resource that is easy to deplete or ruin?through depletion, salinization and pollution